UJI AKTIVITAS ANTIOKSIDAN BUAH SEMANGKA (Citrullus lanatus) DENGAN METODE FRAP - Masdiana Tahir; Anda Cahya Heluth; Harti Widiastuti (Fakultas Farmasi UMI, 2016)
Have been conducted a research about antioxidant activity assay at watermelon (Citrullus lanatus) using FRAP method. Watermelon is known contains vitamin A, B, C, and lycopene. The aim of research were to determine the antioxidant activity relationship between watermelon juice and vitamin C with FRAP method using ascorbic acid as a comparative standard measure by UV-Vis spectrophotometer at a wavelength of 692 nm. The research result was obtained the antioxidant capacity on the watermelon red meat juice 0,1329 mg AAE/g.